Implementasi Nilai-Nilai Kepemimpinan Rasulullah dalam Kepemimpinan Pendidikan Islam di Era Digital - Endar Evta Yuda Prayogi; Hardika Saputra; Rachmat Panca Putera (Reflection : Islamic Education Journal, 2024)
This study explores the integration of Prophet Muhammad's leadership values within Islamic educational institutions, focusing on the challenges and opportunities in the digital age. The primary objective is to analyze how Islamic leadership principles can align with digital advancements while upholding core Islamic values. Using a qualitative approach through document and thematic analysis, this research identifies key challenges, including digital disparities, limited access to technology, and tensions between technological culture and traditional Islamic values. Key strategies are proposed, such as technology-based Islamic leadership training and collaborative efforts to develop digital infrastructure, along with the use of social media as a platform for disseminating Islamic educational values. The findings provide insights into how Islamic educational leadership can adapt in the digital era and suggest future research directions on the role of specific technologies in the application of Islamic leadership.